Clinical bone health among adults with cerebral palsy: moving beyond assessing bone mineral density alone. (17th October 2021) - Whitney, Daniel G; Caird, Michelle S; Clines, Gregory A; Hurvitz, Edward A; Jepsen, Karl J
Abstract : Aim: To understand associations among bone mineral density (BMD), bone mineral content (BMC), and bone area, and their association with fractures in adults with cerebral palsy (CP). Method: This retrospective cohort study included 78 adults with CP with a hip dual energy X‐ray absorptiometry (DXA) from 1st December 2012 to 3rd May 2021 performed at the University of Michigan. Data‐driven logistic regression techniques identified which, if any, DXA‐derived bone traits (e.g. age/sex/ethnicity‐based z‐scores) were associated with fracture risk by sex and severity of CP. BMC‐area associations were examined to study the structural mechanisms of fragility. Results: Femoral neck area was associated with lower age‐adjusted odds ratios (ORs) of fracture history (OR 0.72; 95% confidence interval [CI] 0.49–1.06; p =0.098), while higher BMD was associated with higher odds of incident fracture (OR 3.08; 95% CI 1.14–8.33; p =0.027). Females with fracture had lower area than females without fracture but similar BMC, whereas males with fracture had larger area and higher BMC than males without fracture. The paradoxical BMD‐fracture association may be due to artificially elevated BMD from BMC‐area associations that differed between females and males (sex interaction, p˂ 0.05): males had higher BMC at lower area values and lower BMC at higher area values compared to females. Interpretation: BMD alone may not be adequate to evaluate bone strength for adults with CP. Further research into associations (or integration) between BMC and area is needed. Abstract : This original article is commented by Szlachetka and Myint on page 406 of this issue.